Environmental management with the use of LCA in the Polish energy system = Zarządzanie środowiskowe z wykorzystaniem analizy LCA w polskim systemie energetycznym - Dzikuć, Maciej (Zielona Góra: Faculty of Economics and Management Press)
The article presents an assessment of the Life Cycle Assessment (LCA) and pointed out its advantages in the analysis of the environmental impact of electricity generation. The article also points to the direction of development of the Polish energy sector and pointed out the need to determine the environmental risks associated with the production of electricity.
Keywords: ocena cyklu życia (istnienia); energia elektryczna; ekologia; węgiel; elektrownie; life cycle assessment (LCA); electricity; ecology; coal; power plants